Electromagnetic interference shielding effectiveness of ABS carbon-based composites manufactured via fused deposition modelling. (June 2018) - Schmitz, D.P.; Ecco, L.G.; Dul, S.; Pereira, E.C.L.; Soares, B.G.; Barra, G.M.O.; Pegoretti, A.
Highlights: Electrically conductive 3D-printed components were fabricated via fused deposition modelling. The 3D-printed components presented shielding efficiency near – 17 Db. The electrical conductivity, mechanical properties and EMI SE of 3D-printed parts are discussed in terms of type of filler and FDM's growing direction. 3D-printed components can have superior EMI shielding efficiency upon appropriate selection of FDM's growing direction. Abstract: 3-D printed samples based on acrylonitrile-butadiene-styrene (ABS) loaded with multi-walled carbon nanotubes (CNT), carbon black (CB) and a 50:50 hybrid combination (CNT/CB) were manufactured via fused deposition modelling (FDM). The electromagnetic interference shielding efficiency (EMI SE) of resulting FDM specimens was assessed. Different amounts of CNT, CB and CNT/CB were dispersed in an ABS matrix by melt compounding using an internal mixer. On the basis of the rheological behavior a weight fraction of 3% was selected for the filaments production. The filaments were prepared using a twin-screw extruder and used to feed a commercial FDM machine for 3-D printed specimen's preparation along three different growing directions. The electrical conductivity, the EMI SE and the mechanical properties of the resulting extruded filaments, as well as the 3-D printed specimens, were measured and, they are discussed in terms of the type of filler and growing directions. In general, the conductivity, EMI SE and mechanical properties of 3D printed parts were markedly dependent on the growing direction. Through the experimental findings of this work, an appropriate choice of a polymer nanocomposite formulation alongside the 3-D printing parameters could lead to components manufactured via FDM with optimized EMI SE and mechanical properties.